Assessment of Selected Heavy Metals and Total Organic Carbon in Surface Sediments along Tg. Datu and Sematan Coastal Area - Farah Akmal, Idrus; Fatin Qistina Ally, Zulkifli; Adriana, Christopher Lee (UNIMAS Publisher, 2024)
Tanjung Datu and Sematan Coastal areas were exposed to recreational activities and construction of Pan Borneo Highway, Sarawak, which may receive indirect input of heavy metals and other components into the nearby seawater. The objectives of this study were (1) to determine the concentration of selected heavy metals concentration (Al, Cd, Co, Cr, Cu, Fe, Mn, Ni and Zn) and (2) to assess the TOC in surface sediment at stations between Tg. Datu and Sematan Coastal areas. Samples were digested following the acid digestion method before analysing with the Flame Atomic Absorption Spectroscopy (FAAS, iCE 3000 Series AA) and total organic carbon analyser (TOC, Shimadzu). The results of heavy metals concentration were followed the sequences of Al (537.33 - 432.44 mg/kg) >Fe (6.81 – 110.01 mg/kg) > Cu (11.84 – 13.02 mg/kg) > Ni (5.27 – 6.50 mg/kg) > Co (3.48 – 4.35mg/kg) > Cr (0.39 – 9.18 mg/kg) > Mn (2.57 – 5.47 mg/kg) >Zn (0.38 – 3. 66 mg/kg) > Cd (0.94 – 1.09 mg/kg). For TOC, all stations were followed the sequences of Station G (1.44±0.01 %) > Station B (1.31±0.03 %) > Station C (0.51±0.02 %) > Station E (0.46±0.03 %) > Station D (0.43±0.04 %) > Station A (0.13±0.02 %). Overall, concentrations of heavy metals and TOC were considerably low. Atmospheric and land-based inputs were the main sources for heavy metals around the sampling areas.